Detection of Network Intrusions with the Methods of Pattern Recognition - Федорик, С. И. (Problems of Informatization and Control, 2004)
The problem of protection from network intrusions is analyzed. Method of signatures classification and recognition of intrusion is proposed. Algorithm of comparative estimation of efficiency of various reconnaissance systems for computer network implementation is developed